Possible mechanism of efficient mainstream partial nitritation/anammox (PN/A) in hybrid bioreactors (IFAS) - Trojanowicz, Karol (Environmental technology, 2021)
An explanation of possible mechanism of efficient PN/A in hybrid bioreactors was presented. The bottleneck process is nitritation. Surplus nitrite production by ammonium oxidizing bacteria (AOB) is required for assuring the activity of anammox bacteria and eliminating nitrite oxidizing bacteria (NOB). It will be possible if nitrogen removal rate by AOB (rN_AOB) is higher than NOB (rN_NOB). It was shown that in biofilm AnAOB bacteria should out-compete NOB, whereas nitrogen transformation rates by AOB are usually lower than NOB. However, the growth of r-AOB in activated sludge allows out-selecting NOB. Impact of ammonium-, nitrite-nitrogen and suspended biomass concentration in hybrid PN/A systems on nitrogen removal rates in the temperature ranges from 10°C to 25°C was presented and discussed. Because bulk liquid ammonium nitrogen concentration can be higher in SBR bioreactors (after certain period of time after aeration starts) or in the initial zones of plug-flow systems than in fully mixed systems, conditions for running efficient PN/A are more favourable in intermittently aerated 'IFAS-SBR' or 'IFAS-plug flow' bioreactors